Innovations Techniques Caféicoles Au Burundi : Étude Des Contraintes Socio-Économiques Et Des Conditions D’adoption Et De Diffusion Des Innovations Techniques Dans La Province Kayanza - Ndabarushimana Alexis; Toh Alain; Kouadio Amani Augustin (European Scientific Journal, ESJ, 2016)
This contribution highlights the socio-economic constraints to the adoption and diffusion of technological innovations in coffee farms in Burundi. These constraints are basically related to the sociological environment that structure behaviors of Burundian coffee growers in the process of economic production. In view these sociological contradictions, initiating a typically socio- anthropological approach, this article highlights a set of policy conditions to stimulate the adoption and diffusion of innovations in Kayanza province of Burundi.